Recent developments in Cyprus-EU relations - Bicak, HA (Eastern Mediterranean University Press, 1997)
[Abstract Not Available]
1st International Congress on Cypriot Studies -- NOV 20-23, 1996 -- GAZIMAGUSA, CYPRUS